Going Beyond the Literal: a Longitudinal Study of Metaphorical Conceptualization in Sustainability Reports (Global Journal of Human-Social Science, 2023)
Language expressions are largely shaped by conceptual metaphors By adopting Conceptual Metaphor Theory as a tool this study explores the communicative strategies adopted by a company s outlook on social and environmental responsibility from a longitudinal perspective In more specific terms the article discusses how Structural Orientational and Ontological conceptual metaphors are employed in the communicative strategies adopted by Chevron Co pre- and during the Covid-19 pandemic crisis Chevron is an American join-stock company which operates in the field of power generation and oil refining The qualitative and quantitative li nguistic analysis conducted using the Sketch Engine programme aimed to pinpoint and clarify the ways in which Chevron and Co s use of language creates and communicates metaphors in its Sustainability Reports
Keywords: conceptual metaphor theory; ontological metaphor; orientational metaphor; structural metaphor; sustainability